Efficient photocatalytic hydrogen production over eosin Y-sensitized MoS2. Issue 79 (9th August 2016) - Yin, Mingcai; Wu, Chaojun; Jia, Fangfang; Wang, Lijiao; Zheng, Pengfei; Fan, Yaoting
Abstract : An uncapped and agglomerated MoS2 catalyst was solvothermally synthesized and exhibited excellent hydrogen production activity under sensitization of eosin Y. Abstract : MoS2 is considered as a promising alternative to noble metals for H2 evolution. In this work, a MoS2 catalyst was synthesized via a simple and feasible solvothermal process and characterized by XRD, SEM, TEM and XPS techniques. Though the thus-obtained MoS2 was stabilizing agent-free and composed of relatively large agglomerated particles, it shows superior hydrogen production performance under sensitization of eosin Y (EY), significantly different form earlier reports. Under optimized conditions, the hydrogen production rate was high, up to 35 mmol h −1 g −1, much higher than those of previous reports. We attribute this to its relatively high surface roughness and the small thin petal-like nanosheets constituting the MoS2, which result in more active sites for hydrogen evolution. Meanwhile, the obtained MoS2 shows excellent photostability with the H2 -evolving activity remaining nearly unchanged after 4 cycles.